Resveratrol effects on cancer cells - Souza, Gerlúcia do Nascimento Barbosa de (2022)
Introduction: Resveratrol has been systematically investigated for its anticancer, anti-inflammatory, cardioprotective, neuroprotective and antidiabetic effects indicated by several. Objective: To understand the antineoplastic action of RESV in reducing the development of cancer cells Methodology: This is a literature review with a descriptive approach. Results: From the study of the literature, it was possible to observe the first step towards the extraordinary results that will contribute to open a range of systematic research. Today we have in our favor the technology that benefits us from these exquisite substances from the skin and seed of the grape, incorporating more natural treatments and less damage to the body. Discussion of results: Resveratrol helps fight cancer associated with chemotherapy. Researcher at UFRJ that the use of this substance reduces the amount of the drug to be administered in chemotherapy and minimizes the effects of the explanatory research of the effects. Conclusion: Through the studies carried out, it was possible with RESV that it is a strong ally to play a leading role in terms of providing a new path of knowledge and diligence in favor of cancer therapy.